The Invasion of Europe : The Story Behind D-day - Michie, Allan A. 1915- (New York Dodd, Mead & Company, 1964)
First-hand account of the circumstances and strategy behind the fateful decision to invade Normandy on June 6, 1944
Include Map, Notes and Index
Keywords: World War (1939-1945) -- France--Normandy -- Military campaigns